Reação e resistência de porta-enxertos de tomateiro à murcha de fusário - Cantú, Rafael Ricardo; Rebelo, José Angelo; Milanesi, Paola Mendes; Goto, Rumy [UNESP] (Universidade Federal de Santa Maria, 2014)
The aim of this research was to verify the reaction of tomato rootstocks to race 3 of F. oxysporum f. sp. lycopersici and his resistance to races 1 and 2. It was tested the rootstocks: Guardião, Helper-M, Anchor-T, Dr K, Kagemusha, Block, Magnet and He-man and, as a control, the cultivars 'Kada', 'Santa Clara', 'Gisele', 'BHRS 2,3'. The experimental design was a completely randomized type, with split-plots and 5 replicates. The rootstocks and cultivars were allocated in principal plot, and the 3 races of F. oxysporum f. sp. lycopersici, in the sub-plots. The plants were inoculated and maintained in vegetation house with temperature and humidity controlled. The rootstock was assessed by the severity of disease infection in the xylem. All rootstock were resistant to races 1 and 2 of F. oxysporum f. sp. lycopersici and only Guardian and Block were resistant to race 3.

O objetivo deste trabalho foi verificar a reação de resistência de porta-enxertos e cultivares de tomateiro à raça 3 de F. oxysporum f. sp. lycopersici e a comprovação de sua resistência às raças 1 e 2. Os porta-enxertos testados foram: Guardião, Helper-M, Anchor-T, Dr. K, Kagemuscha, Block, Magnet e He-Man, e, como testemunhas, as cultivares 'Kada', 'Santa Clara', 'Gisele', 'BHRS 2,3'. O delineamento experimental utilizado foi o inteiramente casualizado, com parcelas subdivididas e 5 repetições, sendo os porta-enxertos e as cultivares, alocados na parcela principal e as 3 raças de F. oxysporum f. sp. lycopersici, nas subparcelas. As plantas foram inoculadas e mantidas em casa de vegetação com temperatura e umidade controladas. Os porta-enxertos foram avaliados pela severidade de infecção do fungo no xilema. Todos os porta-enxertos foram resistentes às raças 1 e 2 de Fusarium oxysporum f. sp. lycopersici e apenas Guardião e Block foram resistentes à raça 3.
Reaction and resistance of tomato rootstock to Fusarium wilt
Keywords: Solanum lycopersicon; Fusarium oxysporum f. sp. lycopersici; raças; enxertia; Solanum lycopersicon; Fusarium oxysporum f. sp. lycopersici; races; grafting